Inherence and Denomination in the Trinity - Thom, Paul (European journal for philosophy of religion, 2014)
The present paper describes an ontological square mapping possible ways of combining the domains and converse domains of the relations of inherence and denomination. In the context of expounding and extending medieval appropriations of elements drawn from Aristotles Categories for theological purposes, the paper uses this square to examine different ways of defining Substance-terms and Accident-terms by reference to inherence and denomination within the constraints imposed by the doctrine of the Trinity. These different approaches are related to particular texts of thinkers including Bonaventure and Gilbert of Poitiers.